2003
DOI: 10.1016/s0014-5793(03)00276-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of wheat endoxylanase inhibitor TAXI‐I1, member of a new class of plant proteins

Abstract: Triticum aestivum endoxylanase inhibitors (TAXIs) are wheat proteins that inhibit family 11 endoxylanases commonly used in di¡erent (bio)technological processes. Here, we report on the identi¢cation of the TAXI-I gene which encodes a mature protein of 381 amino acids with a calculated molecular mass of 38.8 kDa. When expressed in Escherichia coli, the recombinant protein had the speci¢city and inhibitory activity of natural TAXI-I, providing conclusive evidence that the isolated gene encodes an endoxylanase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
1
44
2
Order By: Relevance
“…SDS-PAGE analysis under reducing circumstances on dissolved TAXI-I crystals indicates the presence in the crystal of both molecular forms A and B (data not shown (16). These residues are part of loop L HeCq , connecting the longest ␣-helix He present in the structure, with ␤-sheet C2, the outer rim of the C domain (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…SDS-PAGE analysis under reducing circumstances on dissolved TAXI-I crystals indicates the presence in the crystal of both molecular forms A and B (data not shown (16). These residues are part of loop L HeCq , connecting the longest ␣-helix He present in the structure, with ␤-sheet C2, the outer rim of the C domain (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…3B) TAXI-I displays significant sequence similarity with a carrot extracellular dermal glycoprotein (37), a tomato xyloglucanspecific endoglucanase inhibitor protein (38) and with TAXIlike proteins (16) identified in barley (HVXI), rye (SCXI-I to SCXI-IV), and durum wheat (TDXI-I and TDXI-II). In addition, screening of the available data bases revealed that multiple TAXI-I homologous genes also occur in soybean, rice, and Arabidopsis thaliana (16). Several amino acids in the TAXI-I sequence, notably 10 of the 12 cysteines, are generally conserved among all TAXI-I-related sequences suggesting a fundamental structural similarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intricate recognition specificities of XIP-I toward specific xylanases from both GH10 and GH11 families might be the result of plant evolution to counteract the many xylanases secreted by bacteria and fungi, similar to polygalacturonase-inhibiting proteins (33). This could also explain why two different classes of xylanase inhibitors with different specificities and expression patterns occur in cereals (29,34). TAXI is the other type of xylanase inhibitor isolated from wheat and is specific for GH11 xylanases (35).…”
Section: Determinants Of Specificity Of Xip-imentioning
confidence: 99%
“…On the other hand, XIP-type inhibitors with molecular masses of 29-32 kDa, inhibit both family 10 as well as family 11 xylanases, as long as they are of fungal origin [9]. Studies on the molecular identification, isolation and characterization of the TAXI-I gene, together with screening of the available wheat EST libraries, showed clear evidence that TAXIs belong to a newly identified class of plant proteins to which a function as plant protective microbial glycoside hydrolase inhibitor can be suggested [10]. In order to study this class of proteins, their inhibition mechanics and specificities, and their influence in the above mentioned industrial processes, a crystallographic study was undertaken.…”
mentioning
confidence: 99%